Análise da concorrência na rede de concessionárias de automóveis no Estado da Bahia - Pimenta, Luiz José (2011)
The significant changes in world economic situation over the past twenty years, combined with extraordinary movement in the sector of car distribution in Brazil, with the offer of more than forty brands vehicles, against six the early 1990s, gave birth strong competition in the automotive sector. Since then, there was a drastic reduction in the rate of profit network of authorized dealers, resulting in a large number of bankruptcies and transfers stakes in companies. These movements have led utilities to promote profound changes in its traditional paradigm, aiming to adapt the business to a new level of profitability, culminating in an unprecedented process of concentration, as in the automotive industry worldwide. The analysis is undertaken here covers aspects of competition between firms of the network of car dealerships in Brazil and, more importantly, between dealers representing the same brand, even in a limited space, considering theoretical aspects, legal and market presents in the auto industry around the world.